Comparison of Strategies for the Production of FMDV Empty Capsids Using the Baculovirus Vector System - Ruiz, Vanesa (2014)
Recombinant FMDV empty capsids have been produced in insect cells and larvae using the baculovirus expression system, although protein yield and efficiency of capsid assembly have been highly variable. In this work, two strategies were compared for the expression of FMDV A/Arg/01 empty capsids: infection with a dual-promoter baculovirus vector coding for the capsid precursor (P12A) and the protease 3C under the control of the polyhedrin and p10 promoters, respectively (BacP12A-3C), or a single-promoter vector coding the P12A3C cassette (BacP12A3C). Expression levels and assembly into empty capsids were analyzed in insect cells and larvae. We observed that the use of the single-promoter vector allowed higher levels of expression both in insect cells and larvae. Recombinant capsid proteins produced by both vectors were recognized by monoclonal antibodies (mAbs) directed against conformational epitopes of FMDV A/Arg/01 and proved to self-assemble into empty capsids (75S) and pentamers (12S) when analyzed by sucrose gradient centrifugation.